Escoamento óleo-gás em equipamento submarino: influência da fração volumétrica de gás na separação de fases no módulo de bombeio - Buson, Davi Faria (2013)
In the Espírito Santo State’s offshore oil Basins commonly use a Pumping Modules to interconnect the producing oil wells to FPSO unit. These modules have a capsular geometry where oil flows and where different multiphase flow patterns can exist. Depending on the flow pattern formed the phase separation can occur causing defects (e.g the so-called gas locking) in the submersible pumps. The present study aims with the investigation the influence of the gas volume fraction, in a mixture (oil/gas) , on the phases separation phenomena. For this purpose two cases were simulated . The first one, for gas volume fraction of 10 % , and the second one for 40 % . The oil mass flowrate used was 8 kg s−1 . All simulations were carried out by using a CFD software. The multiphase model chosen was the explicit VOF ( "Volume of Fluid ") with a Courant number of 0.25 and time step of 4 x 10−5 s . Three different meshs were evaluated by convergence criteria and element size , always giving priority to a possible formation of a clear interface between the fluids. For the first case 10 % volume fraction , there was no clear separation of the phases, but the formation of an asymmetrical flow pattern , indicated by velocity profiles obtained under various positions and planes. The order of speed in a sector of the capsule varies from 7 m s−1 at the entrance and 1.2 m s−1 to 2.5 diameters length. Furthermore, for volume fraction of 40 % , a clear interface is formed and gas accumulated at the top of the capsule. In this case, for a 2.5 diameters length of capsule, the percentage of gas accumulated in a interval of 4.2 s was 90 % of the quantity incoming in the capsule . Velocity were ranged from 9.8 m s −1 at the entrance and 0.15 m s−1 to 2.5 diameters length . The final considerations suggest that simulations are conducted to obtain actual times of the order of minutes , as the capsule has 50 equivalent diameters in length.